The interplay among sleep patterns, social habits, and environmental cues: insights from the Spanish population and implications for aligning daily rhythms - Bonmatí-Carrión, María-Ángeles; Vicente-Martínez, Jesús; Madrid, Juan Antonio; Rol, Maria Angeles (Frontiers in Physiology, 2024)
Introduction The interplay among sleep patterns, social habits and environmental cues is becoming increasingly more important for public health and wellbeing due to its connection to circadian desynchronization. This paper explores said connections in Spain (which has an official and solar time mismatch), introducing the “Three Times Score” ‒which is based on questions widely used in the field‒ as a complementary tool for exploring the interplay of daily rhythms. Methods The questionnaire covers sleep-related habits, social time, and environmental time. The study includes 9,947 participants (34.89 ± 12.15 y/o, mean ± SD; 5,561 women) from different Spanish regions. Sleep parameters were obtained for work and free days, as well as a modified version of the sleep-corrected midsleep on free days (MBFbc) and a parameter similar to social jet lag, both derived from bed time rather than sleep time. A number of indexes were computed to compare bed and work-related habits, together with natural light/dark cycle, along with the Three Times Score. Mixed-effect regression analysis was used to test whether the biological, social and environmental factors included in the study significantly predicted the sleep-related parameters: bedtime, wake-up time, time in bed and mid-bedtime. Results and discussion Temporal differences were found between work and free days, with waking-up occurring 2 h earlier on work days (7:10 ± 0:01) than on free days (9:15 ± 0:01). Bed times were 1 h earlier on work days (23:46 ± 0:01) than on free days (00:45 ± 0:01), whereas time in bed was over 1 h shorter on work (7 h 23 min) versus free (8 h 29 min) days. Strong correlations were found between work starting time and waking-up and bedtimes on workdays. Women went to bed earlier and woke up later, spending more time in bed. Differences in sleep habits were observed between work and free days across all age groups. The group of younger adults (18–30) reported going to bed later than older and younger groups, especially on free days. Adolescents and young adults also woke-up later than other age groups, especially on free days. Social jet lag (relative to bed time) and desynchronization indexes also varied with age, with younger adult participants exhibiting higher levels. Seasonal differences were limited, with minor variations between winter and summer. According to the multiple regression analysis, social (day type, work start time, alarm clock usage), biological (age, gender, in most cases related to sex) and environmental (sunset time) factors significantly contribute to predicting sleep/bed related schedules. This study provides insights into sleep habits in the Spanish population, introducing the Three Times Score as a complementary tool for exploring the interactions between sleep/bed-related habits, natural darkness and work-related schedules. Understanding this interplay is crucial for developing tailored interventions to improve sleep and wellbeing.